Bacteriome composition analysis of selected mineral water occurrences in Serbia - Šaraba, Vladimir; Dragišić, Veselin; Janakiev, Tamara; Obradović, Vesna; Ćopić, Milica; Knežević, Branislav; Dimkić, Ivica (Archives of Biological Sciences, 2022)
Paper description: The composition of bacterial communities and their physicochemical properties can provide insight into the quality status of mineral waters. Bacterial diversity of mineral waters was studied by metabarcoding analysis of 16S rDNA. Physicochemical analysis of mineral waters was performed. The study provides first insight into the bacterial diversity of selected occurrences based on metabarcoding analysis. Different physiological groups of bacteria were identified among occurrences characterized by higher levels of total dissolved solids and elevated concentrations of chemical compounds. The identified bacteria points to the need for further revitalization of the investigated occurrences. Abstract: Bacterial metabarcoding analysis by 16S rDNA of five occurrences of mineral waters in Serbia (Torda, Slankamen Banja, Lomnički Kiseljak, Velika Vrbnica and Obrenovačka Banja) indicated the presence of a high percentage of the Proteobacteria phylum, followed by the Bacteroidetes phylum. The families Rhodobacteraceae, Burkholderiaceae, Pseudomonadaceae, Methylophilaceae and Moraxellaceae were the most dominant in the bacterial flora of the selected occurrences, whereas the most represented genera were Acinetobacter, Pseudorhodobacter, Pseudomonas, Limnohabitans, Massilia, Limnobacter and Methylotenera. The presence of coliform bacteria was not detected. Alpha diversity analysis revealed that Slankamen Banja and Lomnički Kiseljak were the richest of the selected occurrences, while the mineral waters of Torda, Velika Vrbnica and Obrenovačka Banja were characterized by similar diversity of bacterial communities determined by beta diversity analysis. Physical-chemical analysis revealed the value of total dissolved solids above 1 g/L, as well as elevated concentrations of some metals and non-metals. The research concluded that specific bacteria contribute to the development of biocorrosion and biofouling processes of water intake facilities. In addition, some of these bacteria might be potential indicators of the organic sources of pollution and/or biotechnological natural remediators in the treatment of contaminated waters.